Pengaruh Media Sosial terhadap Minat Berwirausaha dengan Religiusitas sebagai variabel Mediasi pada Mahasiswa Kewirausahaan - Dewi Khadijah; Putra Panji Respati (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
The development of digital technology, particularly social media, has significantly changed how students access information, build networks, and develop perceptions of entrepreneurship. Social media is not only used for communication but also functions as a medium for learning, promotion, and business inspiration that may influence students’ entrepreneurial interest. However, exposure to entrepreneurial content does not always lead directly to entrepreneurial intention without the support of internal factors. One important internal factor is religiosity, which can guide values, decision-making, motivation, and entrepreneurial attitudes. This study aims to analyze the influence of social media on entrepreneurial interest with religiosity as a mediating variable in student entrepreneurship. A quantitative approach was employed by distributing questionnaires to 76 respondents selected through purposive sampling. The data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results show that social media influences entrepreneurial interest (T-Statistic = 1.814) and religiosity (T-Statistic = 7.215), while religiosity influences entrepreneurial interest (T-Statistic = 1.281). These findings indicate that religiosity plays a mediating role in strengthening the influence of social media on students’ entrepreneurial interest. This study contributes to the development of value-based entrepreneurship in the digital era.